2010
DOI: 10.1016/j.ijid.2009.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Type-specific herpes simplex virus-1 and herpes simplex virus-2 seroprevalence in Romania: comparison of prevalence and risk factors in women and men

Abstract: In Romania, HSV-2 seroprevalence was higher in women than men, and was within European limits and lower than that in Africa and the USA. In contrast, HSV-1 seroprevalence was generally higher than that previously recorded in similarly aged populations in Western Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
(27 reference statements)
5
14
1
1
Order By: Relevance
“…Studies from general population and low-risk populations from Eastern Europe showed an HSV-2 seroprevalence that was either comparable to [23] or lower than [24–26] what we observed. One study showed great variations in seroprevalence in Europe, from 24 % in Bulgaria, 14 % in Germany, 13 % in Finland and 11 % in Belgium, to 9 % in the Netherlands, 6 % in the Czech Republic and 4 % in England and Wales [27].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies from general population and low-risk populations from Eastern Europe showed an HSV-2 seroprevalence that was either comparable to [23] or lower than [24–26] what we observed. One study showed great variations in seroprevalence in Europe, from 24 % in Bulgaria, 14 % in Germany, 13 % in Finland and 11 % in Belgium, to 9 % in the Netherlands, 6 % in the Czech Republic and 4 % in England and Wales [27].…”
Section: Discussionsupporting
confidence: 69%
“…[4]. Low education has consistently been associated with HSV-2 seropositivity [24, 28, 32, 37], and smoking has been reported as a risk factor for HSV-2 infection in some studies [28, 34], but not others [24, 37]. For both sexes, we also found such associations, but it did not reach the level of statistical significance in the multivariable analyses, although close for smoking in women.…”
Section: Discussioncontrasting
confidence: 54%
“…[10] Studies have found that women are more susceptible to Herpes progenitalis infection biologically. [11,12] Transmission of the virus from male-to-female was more common than from female-to-male. Moreover, the female genitalia have plenty of soft tissue that is exposed for skin contact, which was presumably more receptive to any virus or sexually transmitted disease.…”
Section: Discussionmentioning
confidence: 99%
“…30 Studies have found that women are more susceptible to HSV-2 infection biologically. 31,32 Transmission of the virus from male to female is more likely than female to male. Moreover, the female genitalia have plenty of soft tissue that is exposed for skin contact, which is presumably more receptive to any virus or STD.…”
Section: Discussionmentioning
confidence: 99%